Strategies to Promote Long-Distance Optic Nerve Regeneration - Yang, Shu-Guang; Li, Chang-Ping; Peng, Xue-Qi; Teng, Zhao-Qian; Liu, Chang-Mei; Zhou, Feng-Quan (Frontiers in Cellular Neuroscience, 2020)
Mammalian retinal ganglion cells (RGCs) in the central nervous system (CNS) often die after optic nerve injury and surviving RGCs fail to regenerate their axons, eventually resulting in irreversible vision loss. Manipulation of a diverse group of genes can significantly boost optic nerve regeneration of mature RGCs by reactivating developmental-like growth programs or suppressing growth inhibitory pathways. By injury of the vision pathway near their brain targets, a few studies have shown that regenerated RGC axons could form functional synapses with targeted neurons but exhibited poor neural conduction or partial functional recovery. Therefore, the functional restoration of eye-to-brain pathways remains a greatly challenging issue. Here, we review recent advances in long-distance optic nerve regeneration and the subsequent reconnecting to central targets. By summarizing our current strategies for promoting functional recovery, we hope to provide potential insights into future exploration in vision reformation after neural injuries.